Kyrgyz Republic : Staff Report for the 2004 Article IV Consultation and Request to Extend the PRGF Arrangement. (IMF Staff Country Reports; Country Report, 2005)
The staff report for the combined 2004 Article IV Consultation on the Kyrgyz Republic highlights the economic developments and external policies. The Kyrgyz Republic's good economic performance owes much to its macroeconomic policies. Fiscal consolidation has helped to stabilize external debt, particularly by containing the externally financed public investment program. The anticipated decline in gold exports calls for actions to diversify exports and preserve cost competitiveness through low inflation and structural reforms to boost productivity growth.